2014
DOI: 10.3917/gen.093.0008
|View full text |Cite
|
Sign up to set email alerts
|

Expérimenter le développement ?

Abstract: À travers la figure de l’économiste française Esther Duflo, on a assisté ces dernières années à la montée en puissance d’une méthode particulière d’évaluation des politiques publiques : les expérimentations aléatoires qui s’inspirent des essais cliniques randomisés en médecine. Cet article revient sur les conditions de leur émergence dans le champ de la lutte contre la pauvreté, avant de s’intéresser plus particulièrement au J-PAL, le laboratoire leader en ce domaine. La pression à la publication, le rapport d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…Soon after Banerjee, Duflo and Kremer received the Nobel Prize, Sanjay Reddy, a professor of economics at the New School argued in Foreign Policy that even though RCTs had become dominant in development economics, they were often conducted ‘at the expense of the world’s poor’ ( Reddy, 2019 ). At a time of nearly unanimous celebration, Reddy and others exposed some of the issues of experimental economics in development contexts, such as the ethical implications of involving human subjects in experiments 3 ( Rayzberg, 2019 ), the scientific robustness of the ‘evidence’ produced ( Bédécarrats et al, 2019 ), and the unintended consequences of scaling up isolated initiatives without taking side effects into account ( Abdelghafour, 2017 ; Jatteau, 2013 ). These discussions invite us to explore the radical re-definition of development policies that RCTs imply.…”
Section: Three Scalability Snapshotsmentioning
confidence: 99%
“…Soon after Banerjee, Duflo and Kremer received the Nobel Prize, Sanjay Reddy, a professor of economics at the New School argued in Foreign Policy that even though RCTs had become dominant in development economics, they were often conducted ‘at the expense of the world’s poor’ ( Reddy, 2019 ). At a time of nearly unanimous celebration, Reddy and others exposed some of the issues of experimental economics in development contexts, such as the ethical implications of involving human subjects in experiments 3 ( Rayzberg, 2019 ), the scientific robustness of the ‘evidence’ produced ( Bédécarrats et al, 2019 ), and the unintended consequences of scaling up isolated initiatives without taking side effects into account ( Abdelghafour, 2017 ; Jatteau, 2013 ). These discussions invite us to explore the radical re-definition of development policies that RCTs imply.…”
Section: Three Scalability Snapshotsmentioning
confidence: 99%
“…In particular, they have shown that the method only applies to a very circumscribed field, and this type of experimental study has many limitations, including biases that may limit the reliability of the results obtained (internal validity threats), limited capacity to explain situations other than the particular case studied (threats to external validity), and the difficulties of generalizing its use (Bédécarrats, Guérin, and Roubaud 2017). Others question the ideal of political and scientific neutrality on which this methodology is based and demonstrate that RCTs on development issues serve primarily to provide donors with an exhaustive list of good and bad development policies and to rank them (Jatteau 2014). They also demonstrate precisely how results may be shaped, both during and after their production, by sociopolitical forces (Faulkner 2014).…”
Section: Introductionmentioning
confidence: 99%
“…La forte circularité entre les élites, les financements et les thématiques au sein de ces espaces est la marque de la philanthropie financière organisée tout au long du vingtième siècle en Amérique du Nord (Lagemann, 1983 ;Zunz, 2012). Par contre, au-delà de ce recours permanent à la science, on observe une variation des savoirs mobilisés et des expertises légitimes d'une décennie à l'autre : mouvement hygiéniste au début siècle où se croisent médecine et urbanisme, sciences sociales soutenues par la Fondation Ford après la Seconde Guerre mondiale, économie du développement et agriculture pour la révolution verte de la Fondation Rockefeller à la même époque, partenariat entre la Fondation Gates et le géant Monsanto dans les dernières décennies, ou encore soutien de l'économie du développement, avec son dernier avatar de la « randomisation », porté par plusieurs fondations (Hewlett, Gates, MacArthur) (Mayneris, 2009 ;Jatteau, 2013).…”
unclassified